Appunti di termodinamica - Olivares, Stefano (Milano University Press, 2023)
Appunti di Termodinamica do not want to be a new text on the subject. They are "notes", sometimes very detailed, which aim to be first useful for making the fundamental elements of thermodynamics one's own. This book is based on the path I have designed up for teaching Thermodynamics for the Degree Course in Physics at the University of Milan. A path undertaken first and foremost by me, as the first and last student, to answer the questions that arise when entering into the study of thermodynamics. Sometimes these are even curious questions, but never trivial ones, which allow those who look carefully to see the world around us with new eyes and which, I hope, will ultimately appears as a new and wonderful world!